Patterns of Students’ Learning Behavior in Fiqh Subject: A Study at MAS Al-Manar Medan - Lestari, Dini; Fanreza, Robie (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the patterns of students’ learning behavior in the Fiqh subject at MAS Al-Manar Medan. The research focuses on identifying the forms of learning behaviors displayed during the instructional process, the factors influencing these behaviors, and the teacher’s classroom management strategies in creating a conducive learning environment. This study employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that students’ learning behaviors fall into three major categories: active behaviors such as asking questions and participating in discussions, passive behaviors such as listening without engagement, and irrelevant behaviors such as being unfocused or engaging in off-task activities. Factors influencing these behaviors include motivation, teacher’s instructional style, classroom atmosphere, and students’ learning readiness. The study recommends the use of active learning strategies to enhance students’ engagement in the Fiqh learning process.